Dampak Telur Pomacea Canaliculata Terhadap Budidaya Ikan di Pakemitan dan Sukamaju Jawa Barat - Haq, Maitsa Siti Najdah; Novitasari, Silvi; Alawiyah, Zaeta Lutfi; RS, Esta Rendra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The presence of Pomacea canaliculata as an invasive species infreshwater tilapia pond ecosystems in rural West Java, particularly in Pakemitan and Sukamaju Villages, has shown a significant impact on ecological balance and the economic productivity of fish farmers. This study to analyze the ecological and socio-economic impacts of P. canaliculata eggs using a qualitative-descriptive approach. Data were collected through direct field observation, structured interviews with local farmers, and review of relevant scientific literature. The findings indicate that P. canaliculata eggs are abundant on moist surfaces around the pond and hatch within 7 14 days, contributing to the degradation of aquatic plants like water hyacinths, a decline in water quality, and increased fish feed consumption. Interviews releaved that farmers struggled to control the spread manually due to snails rapid life cycle and high adaptability. Supporting literature confirms the species voracious feeding behavior and its potential to reduce aquaculture productivity. Based on data synthesis, this study recommends combining manual and biological control strategies through a geo-ecological approach, including routine egg removal, use of natural predators such as ducks, and periodic pond maintenance and cleaning.